Boost Converters’ Proximate Constrained Time-Optimal Sliding Mode Control Based on Hybrid Switching Model - Asghar Taheri; Amir Ghasemian; Hai-Peng Ren (Complexity)
It is well known in the literature studies that the theoretical time-optimal control of boost converters can be achieved using switching surfaces based on the converter’s natural state trajectories. However, this method has two important drawbacks: First, the transient current peak of the time-optimal controller is far beyond the current limitations of related circuit elements in many practical cases. Second, switching based on the converter’s natural trajectories has high computational complexity and high dependence on circuit parameters. In this paper, based on the hybrid dynamical model of the converter and geometrical representation of its corresponding vector fields, a proximate constrained time-optimal sliding mode controller is proposed. The proposed method has a fast response that is near that of a time-optimal controller, with less computational complexity and sensitivity to parameter changes. The proposed method and its relevant theoretical framework are validated on an experimental setup with a boost converter prototype and an eZdsp TMS320F2812 processor board.